Developing Scientific Ethics in Early Childhood Education as a Moral Foundation for Emerging Generations - Sheila Citra Suci (Al-Qalam Institute, 2025)
Early Childhood Education (PAUD) plays a crucial role in shaping children’s character and knowledge base, which significantly impacts their future development. At this stage, children begin to internalise moral and ethical values that will guide their behaviour throughout life. This study adopts a descriptive qualitative approach, involving PAUD educators, parents, and community members who are actively engaged in children’s education. Data were collected through observations, interviews, and document analysis. The main objective of the study is to explore the integration of scientific ethics into the PAUD curriculum and involve all stakeholders in creating a supportive environment for the holistic moral development of children. The findings reveal that ethical principles are widely practised in PAUD settings, contributing to the development of moral values in children. This study’s contribution lies in its emphasis on the importance of embedding scientific ethics in early childhood education, offering new insights into the role of ethics in nurturing responsible and empathetic future generations. The study recommends further collaboration among educators, parents, and communities to foster an environment that supports children’s continuous moral growth.